2021
DOI: 10.3389/fphy.2021.769786
|View full text |Cite
|
Sign up to set email alerts
|

Silty Clay Stabilization Using Metakaolin-Based Geopolymer Binder

Abstract: Geopolymer binders are adjudged as the latest wave of sustainable alkali-activated materials for soil stabilization due to their excellent bonding properties. This study applied metakaolin as a precursor for synthesizing the geopolymer binder by employing the mixture of quicklime and sodium bicarbonate as an alkali activator. The optimal mass mixing ratio of the alkali activator, metakaolin, and silty clay was determined by unconfined compression tests. The stabilization mechanisms of the geopolymer binder wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Some soil has a hard stratum to work on; on the other hand, some have very poor properties to withstand the loading. Additionally, the productivity of building businesses is affected by the mineralogical qualities that speci c soils possess(T.Subramani 2015; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some soil has a hard stratum to work on; on the other hand, some have very poor properties to withstand the loading. Additionally, the productivity of building businesses is affected by the mineralogical qualities that speci c soils possess(T.Subramani 2015; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10 presents the infrared spectrum evolution of the CSFSS over the curing age. It could be found that there was a strong absorption peak near 700 cm −1 during the early curing age, which was related to the bending vibration of Al-O [32]. An absorption peak near 630 cm −1 was also observed, which is commonly caused by the symmetrical vibration of zeolite-like atomic groups.…”
Section: Ftir Spectramentioning
confidence: 92%
“…Figure 15 indicates the impact of different contents of alkaline activator (AA) and MK in binders on the UCS of treated soil [140]. It shows a maximum strength at 7 days by 5% AA and 10% MK, with about 419 kPa as a mean value, then a decrease in strength afterwards.…”
Section: Soilmentioning
confidence: 99%
“…Thus, the optimum content of GB should be 15%, while economically it would be adequate to select 12% as it shows a minor difference in strength from 15% GB. Figure 15 indicates the impact of different contents of alkaline activator (AA) and MK in binders on the UCS of treated soil [140]. It shows a maximum strength at 7 days by 5% AA and 10% MK, with about 419 kPa as a mean value, then a decrease in strength afterwards.…”
Section: Soilmentioning
confidence: 99%